The Relationship between Teacher Factors and Malaysian Undergraduates’ Grammatical Errors in Writing - Khatipah Binti Abdul Ghani; Soo Ruey Shing (Institut Agama Islam Negeri Palopo, 2019)
This study aims to analyse grammatical problems in writing encountered by undergraduates in Malaysian University English Test (MUET), and to determine whether teachers’ teaching backgrounds and teaching methodologies had any impact on the undergraduates’ errors in writing. 335 writing scripts were analyzed in order to identify students’ grammatical errors. Additionally, to analyse the relationship between various teacher factors and students’ grammatical errors in writing, questionnaires were administered to fifteen full-time English teachers in a Malaysian university. The analysis of the scripts revealed that the undergraduates had the most problem in using verbs, followed by nouns, pronouns, prepositions and sentence patterns. Statistical analyses indicated that teachers’ teaching experiences, academic qualifications and teaching approaches had significant impact on the undergraduates’ grammatical problems in writing, to a certain extent. Based on the findings of this study, language teachers are suggested to vary their teaching approaches according to the types of grammatical items and expand the contexts while teaching grammar. It is also recommended that teachers at all levels require retraining periodically for professional development.